Serum amyloid A, a host-derived DAMP in pregnancy? - Lin, Yi-kai; Zhu, Ping; Wang, Wang-sheng; Sun, Kang (Frontiers in Immunology, 2022)
Serum amyloid A (SAA) is one of the acute phase proteins released primarily from the liver in response to infection, inflammation and trauma. Emerging evidence indicates that SAA may function as a host-derived damage-associated molecular pattern (DAMP) protein to sense danger signals in pregnancy. The plasma SAA levels in maternal circulation are significantly increased in normal parturition, particularly in postpartum, as well as in gestational disorders such as premature preterm rupture of membranes, pre-eclampsia, gestational diabetes, and recurrent spontaneous abortion. It is likely that SAA acts as a non-specific DAMP molecule in response to inflammation and trauma experienced under these conditions. Notably, SAA can also be synthesized locally in virtually all gestational tissues. Within these gestational tissues, under the induction by bacterial products, pro-inflammatory cytokines and stress hormone glucocorticoids, SAA may exert tissue-specific effects as a toll-like receptor 4 (TLR4)-sensed DAMP molecule. SAA may promote parturition through stimulation of inflammatory reactions via induction of pro-inflammatory cytokines, chemokines, adhesion molecules and prostaglandins in the uterus, fetal membranes and placenta. In the fetal membranes, SAA may also facilitate membrane rupture through induction of matrix metalloproteases (MMPs)- and autophagy-mediated collagen breakdown and attenuation of lysyl oxidase-mediated collagen cross-linking. SAA synthesized in extravillous trophoblasts may promote their invasiveness into the endometrium in placentation. Here, we summarized the current understanding of SAA in pregnancy with an aim to stimulate in-depth investigation of SAA in pregnancy, which may help better understand how inflammation is initiated in gestational tissues in both normal and abnormal pregnancies.